The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.mex.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A sandwich enzyme-linked immunosorbent assay for the quantitation of human plasma ferritin

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Before concluding this section, it should be noted that numerous commercial optical products exist to qualitatively and quantitatively measure the concentrations of target analytes. These methods include colorimetric assays, fluorometric assays, chemiluminescence assays, and various forms of ELISA kits. Some commonly encountered challenges among commercial assays are the need for expensive kits and tedious sample preparation for labeling . The exceptional optical properties of 2D materials (such as tunable band structure as discussed previously) offer opportunities for their utilization in ultrasensitive, tunable optical biosensors with wide dynamic range, as detailed elsewhere …”
Section: Biosensing and Biomedical Applicationsmentioning
confidence: 99%
“…Before concluding this section, it should be noted that numerous commercial optical products exist to qualitatively and quantitatively measure the concentrations of target analytes. These methods include colorimetric assays, fluorometric assays, chemiluminescence assays, and various forms of ELISA kits. Some commonly encountered challenges among commercial assays are the need for expensive kits and tedious sample preparation for labeling . The exceptional optical properties of 2D materials (such as tunable band structure as discussed previously) offer opportunities for their utilization in ultrasensitive, tunable optical biosensors with wide dynamic range, as detailed elsewhere …”
Section: Biosensing and Biomedical Applicationsmentioning
confidence: 99%
“…It has to be noted that the concentrations that were chosen for each protein were modified based on the literature, and correspond to the amounts that can be found both in the cell culture media and in the cerebrospinal fluid. [19]…”
Section: Resultsmentioning
confidence: 99%
“…This competitive detection method resulted in a detection range between 2.5–350 ng/mL [ 45 ]. Bleicher et al reported a sandwich ELISA using polyclonal antibodies for the quantification of ferritin with a detection range between 3.2–232 ng/mL [ 46 ]. Garg et al reported microfluidics-based nanoparticle-enhanced electrochemical detection by using an integrated electrochemically active screen-printed electrode (SPE) to monitor SF with a detection range between 7.81–500 ng/mL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%